EXPLORING STUDENTS' PROFICIENCY THROUGH PERSONAL CHARACTERISTICS IN MATH LOGIC COURSES USING PEER TEACHING FLIPPED CLASSROOM - Ramadoni Ramadoni; Hafizah Delyana; Melisa Melisa (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Mathematical logic is a mandatory course offered in a range of educational settings. Mathematical logic is a kind of particular understanding. Students must understand the concept of mathematical logic before they can apply it to solve problems. On the other hand, students are divided into two major personality types: extroverts and introverts. Students' personality types influenced their study process. This study was carried out to examine the impact of students' personality types on their conceptual understanding abilities. Where questionnaires for personality examinations and tests for understanding concepts were employed as research instruments. According to research findings, in using the peer teaching flipped classroom model, students' conceptual understanding in math logic courses is strongly affected by personality category. The results of experiments such as peer teaching flipped classrooms exhibit that extrovert students have better conceptual understanding skills than introvert students. On the other hand, students who use the PTFC model are better than students who learn using the conventional models. Creating videos and organizing class discussions has a big impact on students who are outgoing. They can improve their skills while also sharing their knowledge and information with their classmates.